Molecular Charaterisation of Salmonella Serovars Isolated from Poultry - Abd. Mutalib, Sahilah (2001)
Salmonellosis has received considerable amount of attention because public health concerns in third world and developing countries including Malaysia. In Malaysia, the incidence of non-typhoidal salmonellosis is relatively unknown and has not been given much attention. Data collec1ed shows that the incidence of Salmonella species iso1atcd from animals and food sources have increased in recent years especially from poultry sources. One hundred and fourty seven Salmonella isolates belonging to 14 serovars were examined in the present study. Molecular techniques namely random amplified polymorphic DNA-PCR (RAPD-PCR), enterobacterial repetitive intergenic consensus-PCR (ERlC-PCR), polymerase chain reaction-ribotyping and pulsed field gel electrophoresis (PFGE) were used to subtype all the 147 Salmonella isolates at strains leveL Among these techniques. RAPD-PCR was the most superior in distinguishing all Salmonella serovars, followed by PFGE, ERIC-PCR and PCR-ribotyping. The PCR-based methods offered several advan1:ages over PFGE due to its speed, economics, ease to perform, results can be generated within 24 hours and large of samples can be analysed. simultaneously. In contrast, PFGE method was technically tedious, demanding and time consuming. Extensive genetic polymorphism or diversity was observed among strains of Salmonella serovars. In molecular typing for epidemiological studies, the level of the percentage of similarity in cluster analysis is arbitrarily adopted based on the clustering of the strains analysed. In this study, 70% of similarity level was chosen to analyse results obtained in PCR-based and PFGE analysis. Cluster obtained by the peR-based and PFGE typing techniques showed some disagreements in discriminating strains. Several strains that have different RAPD patterns did not necessarily bad similar PFGE. ERIC or PCR-ribotyping patterns. From the present study, it can be concluded that, it is impossible to rely on a single method to determine genetic relatedness among Salmonella serovars for effective epidemiological studies. This study clearly suggests that only a combination of different techniques is able to provide a comprehensive epidemiology of Salmonella serovars, and thus the need for a careful selection of the typing techniques. It has been identify the DNA-based typing methods is most effective for epidemiological studies.